Participatory diagnostic toolkits and crop improvement approaches: participatory methods to assess and use plant genetic diversity in the field. - Mengistu, Dejene Kassahun; Jarvis, Devra I.; Fadda, Carlo (Mimesis, 2022)
In both developing and developed countries, there is increasing in terest in adopting more inclusive and problem-solving participatory re search methods. While there is a wealth of methods and toolkits for con ducting participatory research in the form of scientific articles, books, and manuals, this manual aims to provide a source of information on available toolkits used in conducting participatory research around plant genetic resources (PGR). The manual aims at all those involved in the characterization and utilization of PGR, information collection from participant farmers, and conservation of PGR. The users could be from research centers, universities, farmers’ organizations, government extension agents, and non-governmental organizations (NGOs). The manual presents participatory information gathering tools, di versity assessment, and deployment tools and diversity conservation approaches. Each toolkit has been described in enough detail to enable readers, at different levels, to understand and use them. The manual’s major merit is in presenting different toolkits in one document that are otherwise scattered in several different sources. Different toolkits used to gather information on status of PGR in participatory varietal deploy ment methods are presented to the readers.